Bioconversion of mixed fruit waste as a potential source of biogas and organic fertilizer - Oyelaran, Olatunde Ajani (International Journal of Integrated Engineering, 2018)
This paper investigates the bioconversion of mixed fruit waste as a potential source of biogas and organic fertilizer. The pH of digester liquid, influent and effluent, temperature of gas production volume were observed. In addition to this, TS and VS of the manure before and after digestion were determined. The TS/VS lost in fermenter and efficiencies of VS conversion to gas was also monitored at the end of the study. The study also shows that residue left after the production of biogas is a valuable organic fertilizer that can be used as an alternative to inorganic fertilizer in maize production and soil fertility. Yield of maize was significantly increased over that of the control. Markedly influenced by the application of organo-minerals, NPK fertilizer and their combination as observed from the increased plant height, diameter of plant stem, leaf area and Weight of 1000 kernels compared to the control. Biogas residue has therefore proved to be environmentally friendly and an effective fertilizer. The use of locally available, nutrient rich organic sources is an effective means for improving soil fertility and increasing crop yield in view of the escalating cost of inorganic fertilizers and low fertilizer use efficiency of crops.